2021
DOI: 10.3389/fchem.2021.690520
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photocatalytic Degradation of Perfluorooctanoic Acid by Mesoporous Sb2O3/TiO2 Heterojunctions

Abstract: Perfluorooctanoic acid (PFOA), a typical perfluorinated carboxylic acid, is an emerging type of permanent organic pollutants that are regulated by the Stockholm Convention. The degradation of PFOA, however, is quite challenging largely due to the ultra-high stability of C-F bonds. Compared with other techniques, photocatalytic degradation offers the potential advantages of simple operation under mild conditions as well as exceptional decomposition and defluorination efficiency. Titanium dioxide (TiO2) is one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The photocatalytic performance strongly depends upon the band gap energy, morphology, surface modification, and active sites for the adsorption process. First, 2D sheets of MXene facilitate the fastest charge transport proficiency and offer a large surface area, the MXene became a good supporting agent for CF composite and significantly improved the adsorption ability of CF/MXene composite. , Second, introducing CF into MXene nanosheets avoids the restacking of MXene layers and increases the surface area of the ternary nanocomposite. Third, MXene, with outstanding electric conductivity, has the potential to capture excited electrons, act as a good electron transporter, and move the charges toward reactive sites for chemical reactions.…”
Section: Resultsmentioning
confidence: 99%
“…The photocatalytic performance strongly depends upon the band gap energy, morphology, surface modification, and active sites for the adsorption process. First, 2D sheets of MXene facilitate the fastest charge transport proficiency and offer a large surface area, the MXene became a good supporting agent for CF composite and significantly improved the adsorption ability of CF/MXene composite. , Second, introducing CF into MXene nanosheets avoids the restacking of MXene layers and increases the surface area of the ternary nanocomposite. Third, MXene, with outstanding electric conductivity, has the potential to capture excited electrons, act as a good electron transporter, and move the charges toward reactive sites for chemical reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Yao et al selected a removal rate of PFOA between 20 and 120 min to calculate degradation kinetics and the process of pseudo-first-order kinetics and mesoporous TiO 2 films of 6.3 × 10 −3 min −1 and 3%-Sb 2 O 3 /TiO 2 12.6 × 10 −3 min −1 [46]. It was found that with the addition of 3.6 mmol/L of the PFOA, the degradation rate constantly increases from 0.48/h to 0.88/h [30,87].…”
Section: Kinetic Parametermentioning
confidence: 99%
“…Based on the mechanisms of photocatalytic AOPs for PFAS degradation, strategies for constructing photocatalysts to enhance the degradation process can be summarized as follows: (1) increase the yield of ROS through element doping, introducing heterojunctions, etc. [26,[70][71][72][73]; (2) increase the rate of reaction between ROS and PFASs by using composite materials and controlling their morphology [38]; and (3) expand degradation pathways by generat- In electrocatalytic processes, oxidation primarily occurs on the anode. Therefore, the choice of anode materials (i.e., electrocatalysts) plays a crucial role in electrocatalytic AOPs for PFAS degradation.…”
Section: Photocatalysts In Aops For Pfas Degradationmentioning
confidence: 99%
“…(1) increase the yield of ROS through element doping, introducing heterojunctions, etc. [26,[70][71][72][73]; (2) increase the rate of reaction between ROS and PFASs by using composite materials and controlling their morphology [38]; and (3) expand degradation pathways by generating multiple ROS from advanced photocatalysts [74]. Currently, commonly used photocatalysts for PFAS degradation include titanium dioxide (TiO 2 ), indium oxide (In 2 O 3 ), gallium oxide (Ga 2 O 3 ), bismuth (Bi)-based materials, and their composites [27,75].…”
Section: Photocatalysts In Aops For Pfas Degradationmentioning
confidence: 99%
See 1 more Smart Citation